PSYCHIATRIC CLINICAL PLACEMENT UPON NURSING STUDENTS PERCEIVED KNOWLEDGE IN CARING FOR MENTALLY ILL - Prasetyo, Herry (Nurse Media Journal of Nursing, 2012)
Background: The implementation of a psychiatric clinical placement has been an integral component in Indonesia Nursing Academies. Purpose: The research was to investigate how nursing students’ perceived knowledge in caring for mentally ill patients as a result of their psychiatric clinical placement. Method: A descriptive survey design commonly called non-experimental design was used in this research. Students, who had completed two weeks in a psychiatric clinical placement as a component of mental health nursing subject, were invited to participate. Then, a questionnaire was distributed to nursing students (N=40), giving an overall responses rate of 85 %. Result: The finding revealed that as a result of clinical placement, the majority of nursing students had better perceived knowledge regarding the concept of mental health and mental illness, nursing care plan, medication and providing education towards patient and people in community about mental health. Conclusion: The findings provide evidence for the benefits of such a clinical placement in relation to students’ perceived knowledge in caring for psychiatric patients. Key words: Clinical placement, nursing students, knowledge, mentally ill